Review on natural fibers/HDPE composites: Effect of chemical modification on the mechanical and thermal properties - Mulinari, Daniella R. [UNESP]; Cioffi, Maria Odila H. [UNESP]; Voorwald, Herman J.C. [UNESP] (My University, 2010)
In the recent years, great attention has been dedicated to the exploitation of natural fibers as reinforcement for plastics, replacing fibers synthetic materials. Objectives are not just environmental concerns and consumer pressure but also a unique combination of high performance, great versatility and processing advantages at low cost. However, certain drawbacks such as incompatibility with a hydrophobic polymer matrix, the tendency to form aggregates during processing and poor resistance to moisture reduce greatly the potential of natural fibers to reinforce polymers. On the other hand, various treatments are being used to improve fibre-matrix compatibility. This process is considered critical as a development phase of these materials due to strong interfiber hydrogen bonding, which holds fibers together. Methods for surface modification can be physical or chemical according to superficial modification approach of the fibre. In this review, the main results presented in the literature are summarized, with specific attention on the properties in terms of physical and chemical structure of natural fibers, thermal and mechanical properties, processing performance and final properties of natural fibers reinforcing high density polyethylene matrix. The use of physical and chemical treatments for the improvement of fibers-matrix interaction was also considered. © 2010 by Nova Science Publishers, Inc. All rights reserved.